Isolasi bakteri Escherichia coli pada lawar merah babi di kota Denpasar - Dennis Yulianto; I Dewa Made Sukrama; Made Agus Hendrayana (Intisari Sains Medis, 2019)
Background: An alarming incidence rate of food-borne diseases in Indonesia become more worrible, especially the one which is caused by Escherichia coli. Based on Food and Drug Supervisory Agency or Badan Pengawas Obat dan Makanan (BPOM) in Indonesia, there are 18.144 people who got infected by food-borne illnesses in 2011. These facts are quite alarming for the people who live in Bali and they are more likely to consume lawar merah babi.Â  Lawar merah babi is a traditional Balinese food made from the mix of vegetable, meat, and some other ingredients as well as it is usually mixed by hand which make it susceptible to be contaminated by bacteria such as Escherichia coli. Aim: The study aims to investigate the E. coli contamination within lawar merah in Denpasar. Method: This descriptive cross-sectional study was conducted using 12 samples of lawar merah babi which were sold in 12 different places all across the Denpasar City. These samples were taken to Microbiology Laboratorium at Medical Faculty, Udayana University. There are three variants of dilution for each sample which are 10-1, 10-2, and 10-3. Each sample was cultured using eosin methylene blue agar as the media. Some of the sample without clear representation in the media will go through further identification. The results of Escherichia coli colonization were counted by the total plating count method to produce them in CFU/g for each of the samples.Result: Some of the samples have been contaminated by Escherichia coli (67%) approximately 17x104 CFU/g contamination average level.Conclusion: The samples exceed the contamination limit which is permitted by the BPOM recommendation, where the maximum Escherichia coli contamination level should not exceed over than 3 CFU/g.